1991
DOI: 10.1159/000288416
|View full text |Cite
|
Sign up to set email alerts
|

Daily Stressors and Systemic Lupus erythematosus: A Longitudinal Analysis – First Findings

Abstract: Patients with systemic lupus erythematosus (SLE) and a comparison group of patients with rheumatoid arthritis (RA) completed the Dutch Everyday Problem Checklist and the Dutch Arthritis Impact Measurement Scale measuring physical and psychosocial aspects of illness. Both scales were completed 9 times at 6-week intervals. In addition several hematological and serological parameters were assayed. Analysis over several time points resulted in only weak correlations between the variables under study. The most rema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0
4

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 7 publications
1
23
0
4
Order By: Relevance
“…This is consistent with the findings of Wekking et al (6) that there is a relationship between daily stress and depression in SLE patients in addition to what is known about contributers to psychologic distress in the general population (30,31). While these findings are familiar to mental health professionals, they may be "news" for physicians treating SLE patients.…”
Section: 5)supporting
confidence: 91%
“…This is consistent with the findings of Wekking et al (6) that there is a relationship between daily stress and depression in SLE patients in addition to what is known about contributers to psychologic distress in the general population (30,31). While these findings are familiar to mental health professionals, they may be "news" for physicians treating SLE patients.…”
Section: 5)supporting
confidence: 91%
“…Existem seis estudos prospectivos sobre esse tema, mais adequados na verificação da correlação estudada, mas que diferem bastante quanto à metodologia empregada (44)(45)(46)(47)(48)(49) . Wekking et al seguiram 13 pacientes com LES durante um ano e mostraram que a freqüência e a intensidade de estressores diários correlacionam-se com depressão e ansiedade e número de atividades sociais, mas não com alguns parâmetros de atividade da doença (alterações laboratoriais, como hemograma e anticorpos, escalas de sintomas ou de interferência em atividades cotidianas).…”
Section: Inluência Do Estresse No Lesunclassified
“…Wekking et al seguiram 13 pacientes com LES durante um ano e mostraram que a freqüência e a intensidade de estressores diários correlacionam-se com depressão e ansiedade e número de atividades sociais, mas não com alguns parâmetros de atividade da doença (alterações laboratoriais, como hemograma e anticorpos, escalas de sintomas ou de interferência em atividades cotidianas). Apesar de serem comparados a um grupo de pacientes com artrite reumatóide como controle, o índice de drop-out deste estudo foi muito grande pois apenas cinco pacientes completaram todos os exames laboratoriais (44) . Um outro estudo, realizado através da aplicação de questionários de preenchimento diário por quase dois meses e remetidos via postal, verificou que o estresse estava associado aos sintomas de depressão, raiva e ansiedade e ao aumento da sintomatologia da doença em 41 pacientes, embora não tenha usado medidas confiáveis de piora da doença ou de presença de estressores (45) .…”
Section: Inluência Do Estresse No Lesunclassified
“…Specifically, diverse studies have shown that stress is one of the environmental factors that can cause a worsening in lupus [2][3][4][5][6][7][8]. Although the role of stress in this illness appears clear, at first, there was certain controversy about the nature of the stressors, as some authors supported the theory that daily stress (not organizing time well, problems in social relationships...etc.)…”
Section: Introductionmentioning
confidence: 99%